The National Comprehensive Governance for epilepsy prevention and control in China. Issue 1 (8th November 2021) - Li, Shichuo; Wang, Yuping; Wang, Wenzhi; Zhou, Dong; Zhang, Hui; Duan, Lirong; Ding, Ding; Jiang, Yuwu; Wang, Yi; Liu, Xiaoyan; Hong, Zhen
Abstract: This article describes "the national comprehensive governance for epilepsy prevention and control in China" as an example of a strategic working program for the prevention and control of epilepsy at a national level. The comprehensive governance includes 10 key elements: epilepsy centers' consortium and three tier diagnosis/treatment network; rural and urban community projects on epilepsy care; awareness, publicity, and education; big data platform; development of telemedicine; team and capacity building; strengthening epilepsy research; developing and strengthening partnership; coordination with government; and international collaboration.